ANALISIS PENGARUH ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR DI KELAS III SDN 173419 POLLUNG - Daliani, Muhammad; Selvianita Tarigan, Putri; Simanjuntak, Nurkhairati (Jurnal Curere, 2024)
Primary school education is formal education given to every individual. The age of the students ranges from 7 to 13 years, this is still categorized as children. At this age, an individual is still interested in games, so it is difficult for an educator to create a peaceful and interesting learning atmosphere to foster students' learning motivation. Using the Ice Breaking method is expected to be useful in refreshing students' minds and fostering enthusiasm for learning. Ice breaking is an activity that changes a tense atmosphere into enthusiasm and attracts someone's attention to foster learning motivation that seems fun so that success is achieved in the learning process.This research was conducted in Class III of SDN 173419 Pollung. With this type of quantitative research, the research design is pre-experimental, namely a One Group design with Pre-Test and Post-Test (One Group Pre-Test and Post-Test Design). The data analysis used in this research is the product moment correlation test. The statistical technique used is Pearson Correlation Product Moment. The aim of this research is to analyze the effect of ice breaking on the motivation of dozens of elementary school students.